Human capital analysis at sme development agency in malaysia: skills, knowledge, attitude, and performance (SKAP) perspectives - Ramli, Lokman Effendi; Osman-Gani, AAhad M. (İbrahim Güran Yumuşak, 2013)
The vision of one of the prominent SME development agency in Malaysia is to become a premier organization in developing local SMEs to grow to be more innovative, resilient, and competitive to compete locally and globally. To achieve these, the agency had conducted an assessment exercise identifying the current levels of SKAP. This paper is to highlight the findings of this study which conducted from November 2011 to February 2012. The study uses the technique of 360 Assessment Feedback and the survey approach to collect the required data and analyzed by using AHP technique.